Surplus vitamin B12 use does not reduce fatigue in patients with Irritable Bowel Syndrome or inflammatory bowel disease: A randomized double-blind placebo-controlled trial. (February 2018) - Scholten, Anne-Marie; Vermeulen, Esther; Dhonukshe-Rutten, Rosalie A.M.; Verhagen, Teuni; Visscher, Angeline; Olivier, Anouk; Timmer, Lilian; Witteman, Ben J.M.
Summary: Objective: In non-conventional care, high doses of vitamin B12 supplementation are used for the treatment of fatigue even in case of normal vitamin B12 blood levels. We performed a randomized placebo controlled trial to investigate the effect of surplus oral vitamin B12 supplementation on fatigue in patients with IBS or IBD. Methods: This randomized double-blind, placebo-controlled trial included 95 out-clinic IBS and IBD patients with deactivating fatigue and normal vitamin B12 blood levels (≥150 pmol/l) aged 18–65 years. Participants were randomly assigned to receive 1000 μg vitamin B12 daily or a placebo supplement for 8 weeks. The primary outcome measure was fatigue (Checklist Individual Strength (CIS)). In addition, measures of quality of life and depression were examined. Results: No significant difference in scores of the CIS subscale 'subjective fatigue' was observed between the intervention group and the control group with changes in scores of −8.1 ± 9.5 and −8.3 ± 10.6 (95% CI −11.65 to 6.71), respectively. The scores on the CIS subscale ' motivation' improved with a significant change in scores of −2.2 ± 4.6 (95% CI −4.4 to −0.04). No significantly increased scores were observed for depression or quality of life in the intervention group compared to the control group. Conclusion: This study did not confirm the expected effect of non-conventional surplus vit B12 supplementation on fatigue in IBS or IBD patients. In addition, no positive effect was observed on depression or quality of life. We conclude that surplus treatment with vitamin B12 in IBS and IBD patients suffering from fatigue has no beneficial clinical effect.